Chiral Metal–Organic Framework Hollow Nanospheres for High‐Efficiency Enantiomer Separation. Issue 12 (17th May 2018) - Wang, Xiaoshi; Zhu, Yanan; Liu, Jian; Liu, Chang; Cao, Changyan; Song, Weiguo
Abstract: Chiral ZIF‐8 hollow nanospheres withd ‐histidine as part of chiral ligands (denoted as H‐d ‐his‐ZIF‐8) were prepared for separation of (±)‐amine acids. Compared to bulkd ‐his‐ZIF‐8 without a hollow cavity, the prepared H‐d ‐his‐ZIF‐8 showed 15 times higher separation capacity and higher ee values of 90.5 % for alanine, 95.2 % for glutamic acid and 92.6 % for lysine, respectively. Abstract : How to approach a separation : Chiral ZIF‐8 hollow nanospheres withd ‐histidine as part of chiral ligands were prepared for separation of (±)‐amine acids with high separation capacity and excellent ee values.